Improvement of the quality of life: experience with climacteric women from the Villa Algre Health Clinic, Temuco, Chile - Póo, Ana María; Vizcarra, Beatriz (Revista Chilena de Salud Pública, 2005)
<!–[if gte mso 9]> Normal 0 21 false false false ES-CL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> The objective of the present article is that of describing the experience acquired with the application of an integral care program to women in their climacteric period, developed as of the year 2000 in the Villa A leg re Health Clinic of the commune of Temuco. The main objective of this program is that of romoting the improvement of the quality of life of consulting women, favoring both their physiological and their psychological adjustment. One of the outstanding features of the program is the psychosocial group intervention aiming at easing the establishment of supporting networks and the development of the participants’ potentials. The experience of 20 women presenting spiritual and/or anxiety disturbances, is described. Their participation in the group began in 2002. Early in the year 2003 they obtained corporate existence, a fact which allowed them to link in with social networks and postulate to different projects. The success of the program surpassed the initial objectives because the women not only overcame their symptoms, they also achieved group cohesion and reinforcement of both their physical and psychological space. This achievement was related to the way in which the workshop was developed, the key element having been the creation of a climate of acceptance and respect, and the confidence of the professionals in the abilities and resources of the participants. This way of working reduces the paternalism of professionals and the dependence of the users, thus favoring the fact that the efforts invested in the promotion of the community organization in terms of improving the quality of life will have a permanence in time.